2001
DOI: 10.1037/0021-843x.110.1.179
|View full text |Cite
|
Sign up to set email alerts
|

Homophobia and physical aggression toward homosexual and heterosexual individuals.

Abstract: This study examined the relationship between homophobia (defined as self-reported negative affect, avoidance, and aggression toward homosexuals) and homosexual aggression. Self-identified heterosexual college men were assigned to homophobic (n = 26) and nonhomophobic (n = 26) groups on the basis of their scores on the Homophobia Scale (HS; L. W. Wright, H. E. Adams, & L A. Bernat, 1999). Physical aggression was examined by having participants administer shocks to a fictitious opponent during a competitive reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
101
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 94 publications
(126 citation statements)
references
References 25 publications
(40 reference statements)
23
101
1
1
Order By: Relevance
“…Bernat et al, 2001;Parrott and Zeichner, 2005;Patel et al, 1995]. The present results are consistent with these studies.…”
Section: Discussionsupporting
confidence: 95%
See 4 more Smart Citations
“…Bernat et al, 2001;Parrott and Zeichner, 2005;Patel et al, 1995]. The present results are consistent with these studies.…”
Section: Discussionsupporting
confidence: 95%
“…In terms of the sexual prejudice model, previous research showed that sexually prejudiced men, in comparison with nonsexually prejudiced men, become angry when they are in the presence of gay men [e.g. Bernat et al, 2001;Parrott et al, 2006;Van de Ven et al, 1996]. Indeed, this study found that sexual prejudice was positively associated with a higher likelihood to experience anger in response to gay men.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations